2018
DOI: 10.1016/j.radonc.2017.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the primary tumour Clinical Target Volumes (CTV-P) in laryngeal, hypopharyngeal, oropharyngeal and oral cavity squamous cell carcinoma: AIRO, CACA, DAHANCA, EORTC, GEORCC, GORTEC, HKNPCSG, HNCIG, IAG-KHT, LPRHHT, NCIC CTG, NCRI, NRG Oncology, PHNS, SBRT, SOMERA, SRO, SSHNO, TROG consensus guidelines

Abstract: Implementation of these guidelines in the daily practice of radiation oncology should contribute to reduce treatment variations from clinicians to clinicians, facilitate the conduct of multi-institutional clinical trials, and contribute to improved care of patients with head and neck carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(153 citation statements)
references
References 47 publications
3
148
0
2
Order By: Relevance
“…Rigorous quality assurance of both target delineation and delivery remain critical particularly with advanced technology such as stereotactic RT. CTV construction by 1 cm volumetric expansion of the GTV was likely sufficient in the vast majority of cases and is consistent with recently published international consensus guidelines; pathology studies have found nearly all microscopic tumor infiltration within 10 mm of the tumor . Similarly, target delineation was consistent with recommended guidelines (contrast‐enhanced planning CT fused with a diagnostic MRI) and image‐guidance was state‐of‐the‐art (cone beam CT, and for the SBRT boost, spinal tracking using orthogonal X‐rays), such that these were not likely factors in the high out‐of‐field recurrence rates.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Rigorous quality assurance of both target delineation and delivery remain critical particularly with advanced technology such as stereotactic RT. CTV construction by 1 cm volumetric expansion of the GTV was likely sufficient in the vast majority of cases and is consistent with recently published international consensus guidelines; pathology studies have found nearly all microscopic tumor infiltration within 10 mm of the tumor . Similarly, target delineation was consistent with recommended guidelines (contrast‐enhanced planning CT fused with a diagnostic MRI) and image‐guidance was state‐of‐the‐art (cone beam CT, and for the SBRT boost, spinal tracking using orthogonal X‐rays), such that these were not likely factors in the high out‐of‐field recurrence rates.…”
Section: Discussionsupporting
confidence: 83%
“…CTV construction by 1 cm volumetric expansion of the GTV was likely sufficient in the vast majority of cases and is consistent with recently published international consensus guidelines; pathology studies have found nearly all microscopic tumor infiltration within 10 mm of the tumor . Similarly, target delineation was consistent with recommended guidelines (contrast‐enhanced planning CT fused with a diagnostic MRI) and image‐guidance was state‐of‐the‐art (cone beam CT, and for the SBRT boost, spinal tracking using orthogonal X‐rays), such that these were not likely factors in the high out‐of‐field recurrence rates. Although reduction of the CTV for the SBRT boost based on tumor response following the IMRT phase may theoretically increase out‐of‐field failures, this is not likely a contributing factor to the out‐of‐field failures in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Increasing diagnostic capabilities and accordingly updating “intermediate dose” target delineation may help to reduce such failures. One such attempt has been recently made in the formulation of consensus guidelines to delineate various TVs …”
Section: Discussionmentioning
confidence: 99%
“…Target volumes will be delineated based on international recommendations [22], [23] after manual rigid registration with the PET planning CT and an MRI if available.…”
Section: Methodsmentioning
confidence: 99%